Untitled (African Knowledges and the History Publication since the 1970s)
Various music videos, includes advertisement break: Evelyn King - "Day To Day"; Donald Newkirk - "I Desire"; Michel'le - "No More Lies"; Tina Turner - "The Best"; AC Black Whisky - "Funky Situation"; Tektronic - "Pump Up the Jam"; Gloria Estefan & The Miami Sound Machine - "Get On Your Feet".
Keywords: Music